2009
DOI: 10.1111/j.1745-7599.2008.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness assessment of older adults in the primary care setting

Abstract: Purpose:  To explore the relationships between the physical fitness and the demographic characteristics, general health and well‐being, social support, and physical activity in a group of community‐dwelling older adults. This study also assessed the feasibility of obtaining physical fitness measures in the primary care setting. Data sources:  Thirty‐four persons older than 60 years completed self‐report measures and the Senior Fitness Test (SFT), a battery of fitness measures normed for older adults. Self‐repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 25 publications
(25 reference statements)
1
26
1
16
Order By: Relevance
“…The mean score for the PASE-C in our sample was below reported PASE-C scores in other elderly populations such as the Japanese [28], Americans [14] and Canadians living in Saskatoon [12], but our values were relatively close to those reported for the Dutch population [27]. It is difficult to determine if the low PASE-C scores reflects a sedentary lifestyle among the elderly Chinese populations residing in Vancouver, or if the differences are more related to study group demographics that affect physical activity such as older age, decreased income, and education level [17].…”
Section: Mean Score and Contributing Demographic Factorscontrasting
confidence: 69%
See 2 more Smart Citations
“…The mean score for the PASE-C in our sample was below reported PASE-C scores in other elderly populations such as the Japanese [28], Americans [14] and Canadians living in Saskatoon [12], but our values were relatively close to those reported for the Dutch population [27]. It is difficult to determine if the low PASE-C scores reflects a sedentary lifestyle among the elderly Chinese populations residing in Vancouver, or if the differences are more related to study group demographics that affect physical activity such as older age, decreased income, and education level [17].…”
Section: Mean Score and Contributing Demographic Factorscontrasting
confidence: 69%
“…Conversely, increased physical activity is associated with, among others; a healthy body mass index (BMI), [11] better mental health [12,13] dynamic balance [14] and a decreased risk of falls [15]. Despite the obvious health benefits of physical activity, 63% of all Canadians are not sufficiently active to benefit their health [16] with 17% of those under the age of 64 being completely inactive compared to 29% of adults 65 and older [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is concluded that activity is important for successful aging (Menec, 2003;Agahi, & Parker, 2008;Townsend & Polatajko, 2007;Bassett, Bourbonnais, & McDowell, 2007) and that physical activity leads to increased strength, endurance, and balance (Purath, Buchholz, & Kark, 2009) as well as less depressive symptoms (Salguero, Martínez-García, Molinero, & Márquez, 2010). Increasing the level of preventive interventions among relatively healthy elderly people is an area of concern for occupational therapists in primary care.…”
Section: Association Of Occupational Therapists 2002) the Canadian mentioning
confidence: 99%
“…Past research identifies that healthcare providers can play a key role in encouraging and supporting physical activity with the older adult population [1821]. Specifically, when healthcare providers encourage physical activity, moderately disadvantaged and minority participants can overcome barriers to physical activity [19].…”
Section: Resultsmentioning
confidence: 99%